2014
DOI: 10.1186/1756-3305-7-221
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of Strongyloides stercoralis in Takeo Province, Cambodia

Abstract: BackgroundThe threadworm Strongyloides stercoralis, the most neglected helminth, affects an estimated 30-100 million people worldwide. Information on S. stercoralis infection is scarce in tropical and sub-tropical resource poor countries, including Cambodia. We determined S. stercoralis infection prevalence and risk factors for infection in the general population in Southern Cambodia.MethodsA cross-sectional study was carried out between January and April 2011 among 2,861 participants living in 60 villages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
56
4
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 30 publications
12
56
4
2
Order By: Relevance
“…In the present study, the observed prevalence of S. stercoralis was significantly higher in males than in females, which is in accordance with the previous study carried out among indigenous people in Peninsular Malaysia [4] as well as in other countries, including Cambodia [9,10], Thailand [7,8], China [11], and Taiwan [26]. This is most likely due to agricultural practices in the surveyed communities.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the observed prevalence of S. stercoralis was significantly higher in males than in females, which is in accordance with the previous study carried out among indigenous people in Peninsular Malaysia [4] as well as in other countries, including Cambodia [9,10], Thailand [7,8], China [11], and Taiwan [26]. This is most likely due to agricultural practices in the surveyed communities.…”
supporting
confidence: 92%
“…Moreover, most of the previous studies were carried out mainly among rural communities in Peninsular Malaysia with prevalence rate ranging from 1.2% to 1.7% [4–6]. As for Thailand in particular, the epidemiology of S. stercoralis has been studied in some detail with prevalence ranging between 2.3% and 28.9% [7,8] and other countries, including Cambodia (10.3–21%) [9,10], China (11.7%) [11], and Japan (5–10%) [12]. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…stercoralis infections and sanitation has rarely been studied so far. Varying results were obtained mostly from cross-sectional studies, which either found no association or a decreased risk associated with defecation in or access to improved latrines [22, 3436]. In our study, we found a strong impact of sanitation coverage in combination with treatment which explained the differences in infection rates at follow-up across villages.…”
Section: Discussioncontrasting
confidence: 38%
“…Yet, the prevalence we observed is also substantially higher than that of other studies using the similar diagnostic approaches. Two recent studies in Kandal and Takeo provinces in Cambodia reported that about a quarter (24.4%) of schoolchildren and 21.0% of the general population were infected, respectively [16], [35]; while Steinmann et al, and Knopp et al found a prevalence rate of 11.7% in a village in Yunnan, China and of 10.8% among schoolchildren in Zanzibar, respectively [39], [40]. Hence, other factors such socioeconomic and sanitary conditions are likely to contribute to the differences observed.…”
Section: Discussionmentioning
confidence: 99%